A slotted random request scheme for connectionless data transmission in bluetooth low energy 5.0 - Shan, Gaoyang; Roh, Byeong hee (Journal of Network and Computer Applications, 2022)
Bluetooth low energy (BLE) is a personal area network (PAN) technology that has been widely implemented in various Internet of Things (IoT) services. BLE defines a connectionless communication method based on request–response to more effectively adapt to services with high flexibility requirements. This communication method can be divided into three steps: the neighbor discovery process (NDP), scan request, and scan response. First, the NDP enables a device known as the scanner to discover another device known as the advertiser nearby. In the second step, the scanner sends a scan request to the advertiser which, after receiving the scan request, sends a data packet in response. Unfortunately, this method is flawed in that the simultaneous discovery of an advertiser by multiple scanners would cause the request packets they send to collide with high probability. In fact, these collisions may always occur when scanners continue to discover common advertisers. To solve this problem, various schemes have been proposed to reduce the probability of a collision. However, these schemes are only suitable for application scenarios with fewer scanners; when more scanners are present, their latency and energy consumption increase rapidly. This prompted us to propose a scheme to improve the performance of the connectionless communication method. In addition, convex optimization was used in the proposed model to minimize the transmission delay and energy consumption. The final simulation results prove that the proposed scheme effectively reduces the delay and the energy consumption when many scanners are involved.
Keywords: Bluetooth low energy; Bluetooth low energy 4.2; Bluetooth low energy 5.0; Communication method; Connection-less communication; Energy-consumption; Lower energies; Neighbor discovery; BLE 4.2; BLE 5.0; Bluetooth low energy; Connectionless communication; Internet of Things